2018
DOI: 10.1051/0004-6361/201731711
|View full text |Cite
|
Sign up to set email alerts
|

Fossil group origins

Abstract: Context. It is thought that fossil systems are relics of structure formation in the primitive Universe. They are galaxy aggregations that have assembled their mass at high redshift with few or no subsequent accretion. Observationally these systems are selected by large magnitude gaps between their 1st and 2nd ranked galaxies (∆m 12 ). Nevertheless, there is still debate over whether or not this observational criterium selects dynamically evolved ancient systems. Aims. We have studied the properties of the near… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…Adami et al (2012) also computed the LF for two FG, finding that their faint-end slope is relatively flat, but without giving numbers. Finally, Aguerri et al (2018) studied the spectroscopic LF of RXJ075243.6+455653, finding α = −1.08 ± 0.33.…”
Section: Luminosity Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adami et al (2012) also computed the LF for two FG, finding that their faint-end slope is relatively flat, but without giving numbers. Finally, Aguerri et al (2018) studied the spectroscopic LF of RXJ075243.6+455653, finding α = −1.08 ± 0.33.…”
Section: Luminosity Functionsmentioning
confidence: 99%
“…Another possibility is that FGs could lack dwarf galaxies for differences in their accretion time. In fact, Aguerri et al (2018) found that the large-scale environment of FGS03 is very rich, so the flat LF found could be explained if the dwarf population are still trapped in nearby groups, awaiting to be merged with the FG. In this context, FGs would be systems in early stages of their mass assembly.…”
Section: Luminosity Functionsmentioning
confidence: 99%
“…redshift by using multi-wavelength observations. To date, the collaboration has published results on the properties of the BCGs (Méndez-Abreu et al 2012;Zarattini et al 2014), on their dark matter halos (Girardi et al 2014;Kundert et al 2015), on the galaxy population (Zarattini et al 2015(Zarattini et al , 2016Aguerri et al 2018), and on the comparison between observations and current cosmological simulations (Kundert et al 2017). Here, we focus our attention on the stellar populations of two BCGs in FGs, namely NGC 6482 and NGC 7556.…”
Section: Galaxymentioning
confidence: 99%
“…As the number of FGs increased, their observational properties became clearer. In particular, many studies focused on the properties of the hot intracluster component (Khosroshahi et al 2007(Khosroshahi et al , 2014Proctor et al 2011;Harrison et al 2012;Girardi et al 2014;Kundert et al 2015) or on the properties of the satellite galaxy population (Khosroshahi et al 2006(Khosroshahi et al , 2014Mendes de Oliveira et al 2006;Aguerri et al 2011Aguerri et al , 2018Adami et al 2012;Lieder et al 2013;Zarattini et al 2014Zarattini et al , 2015Zarattini et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The project studied the properties of the BCGs in FGs (Méndez-Abreu et al 2012), the X-ray-versusoptical scaling relations (Girardi et al 2014), the global X-ray scaling relations (Kundert et al 2017; hereafter Paper VI), the dependence of the luminosity function on the magnitude gap (Paper V), the presence of substructures in FGs (Paper VII), and the stellar populations in FG BCGs (Corsini et al 2018). Moreover, we presented the case of a transitional fossil system in Aguerri et al (2018).…”
Section: Introductionmentioning
confidence: 99%